PENGATURAN WASIAT WAJIBAH TERHADAP ANAK ANGKAT MENURUT HUKUM ISLAM - Ade Kurniawan Akbar (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2019)
Abstract: The inheritance law is an approved law regarding the transfer of assets issued by a person who is delayed and the consequences for his heirs. In a will which is also called a mandatory will, a will is usually given to people who are not heirs. Mandatory obligation is a mandatory requirement for every Muslim to provide part of the inheritance to family members needed and for adopted children. The type of research used in this journal is a normative legal research method. Normative research or library research is legal research conducted by examining library material or mere secondary data. Normative legal research is to consider the relationship between the legal sciences and positive law. Mandatory wills are made as a basis by the Compilation of Islamic Law to provide part of the inheritance's inheritance for adopted children who may not be given a will by the testator, or adoptive parents who are not given a will by the heir (adopted child). The existence of mandatory provisions in the Compilation of Islamic Law is a bridge that determines the inequality that has occurred so far between adopted children and adoptive parents who have not inherited from each other, because there is indeed no provision to inherit each other between.Keywords: Mandatory Testament; Adopted Child; Islamic law;